Human‐driven geomorphological processes and soil degradation in Northwest Argentina: A geoarchaeological view. (29th August 2018) - Sampietro Vattuone, Maria; Peña Monne, José Luis; Roldán, Jimena; Maldonado, Mario; Lefebvre, Maria; Vattuone, Marta
Abstract: The study of human‐driven processes is useful to gain a better understanding of the long‐term evolution of land degradation, soil erosion, and geomorphology as well as resource availability for human settlement. The objective of this paper is to identify the long‐term results of human impact on the vulnerable dryland ecosystems in Northwest Argentina, specifically to analyze the consequences of the spread and consolidation of the agricultural way of life on the landscape. To reach this objective, a multiproxy interdisciplinary geoarchaeological study was conducted to link an evolutionary geomorphological model with the soil development and degradation, peopling, and land use change during the Upper Holocene and integrate distinct areas of the Tafí Valley region, which is the most studied area, other neighbouring valleys, and the Puna. The analyses identified positive human‐driven impacts that led to a general degradation of the landscape during the agricultural Prehispanic Period, dated between ca. 2000 and 500 bp . This degradation is manifested by accelerated morphogenesis, mainly fine‐grained accumulated sediments, thick deposits, and the presence of human debris interbedded with the natural sediments. The success of the productive agricultural systems that expanded during the Formative Period led to a gradual increase in the demographic density, resulting in extensive environmental degradation due to overexploitation of the drylands of Northwest Argentina, in some cases increased by adverse climatic changes.